Sistem Kontrol Kadar Amonia Dan Tinggi Air Pada Kolam Penangkaran Tukik Penyu - Riego Pitos Hababil; Budi Rahmadya (CHIPSET)
Turtles are also one of the animals whose population is decreasing day by day due to several factors ranging from climate change, disease, environmental damage and inadequate processing of conservation techniques and so on. With the status of turtles being endangered, special attention is needed for turtles in the form of cultivating turtles, especially when the turtles are still 0-2 years old or known as hatchlings. One of the important indicators in hatchling cultivation requires good seawater quality management. One of the parameters of good seawater quality is ammonia levels. This ammonia level can be formed naturally by metabolic wastes and also food waste that decomposes in the water which results in the formation of ammonia levels. In turtle hatchling ponds it is also necessary to adjust the water level in the pond with a height of 5cm - 10cm because newborn hatchlings cannot dive. The importance of regular water quality control such as ammonia levels and water level in ponds is very important for the success of hatchling cultivation. Therefore, a research on monitoring and controlling systems for ammonia levels and water levels using the TCS3200 color sensor is carried out to read the change in water color after administration of an ammonia test solution which will show the value of ammonia levels in water. Previously, water sampling was carried out by DC pumps and ultrasonic sensors to detect water level. Where this system can monitor and control ammonia levels and height automatically and the results can be viewed using a smartphone through the Blynk application